2020
DOI: 10.1007/s00441-020-03318-2
|View full text |Cite
|
Sign up to set email alerts
|

Isthmin1, a secreted signaling protein, acts downstream of diverse embryonic patterning centers in development

Abstract: Extracellular signals play essential roles during embryonic patterning by providing positional information in a concentration-dependent manner, and many such signals, like Wnt, fibroblast growth factor (FGF), Hedgehog (Hh), and retinoic acid, act by being secreted into the extracellular space, thereby triggering receptor-mediated responses in other cells. Isthmin1 (ism1) is a secreted protein whose gene expression pattern coincides with that of early dorsal determinants, nodal ligand genes like sqt and cyc, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Notably, sqt and boz upregulate ISM1 expression even when β-catenin is blocked, which, combined with previous studies reporting that β-catenin is a transient signaling molecule, suggests that the Wnt/β-catenin pathway may not be required for ISM1 activation (Kesavan et al 2021). However, in contrast to these early observations, late ISM1 expression appears to be independent of nodal signaling (Kesavan et al 2021), suggesting that ISM1 expression is temporally controlled by a different signaling system.…”
Section: Dynamic Expression Of Ism1mentioning
confidence: 73%
See 4 more Smart Citations
“…Notably, sqt and boz upregulate ISM1 expression even when β-catenin is blocked, which, combined with previous studies reporting that β-catenin is a transient signaling molecule, suggests that the Wnt/β-catenin pathway may not be required for ISM1 activation (Kesavan et al 2021). However, in contrast to these early observations, late ISM1 expression appears to be independent of nodal signaling (Kesavan et al 2021), suggesting that ISM1 expression is temporally controlled by a different signaling system.…”
Section: Dynamic Expression Of Ism1mentioning
confidence: 73%
“…It has been confirmed that ISM1 and Fgf-8 genes are expressed at very similar sites, with partially overlapping or co-expressing expression domains at the anterior margin of the neural plate, MHB, gill arch, posterior mesencephalon, and ear capsule in African clawed frogs (Pera et al 2002 ). The expression domains of ISM1 in zebrafish embryos include the dorsal edge of the embryo, the dorsal hypoderm, the posterior medial part of the mesoderm, the MHB, and the notochord; these ISM1 expression locations are very similar to those of Fgf-8 (Kesavan et al 2021 ). This also reaffirms the conserved expression of ISM1 across species and the possible important role of ISM1 in neurological development during the embryonic stage.…”
Section: Overview Of Isthmin-1mentioning
confidence: 99%
See 3 more Smart Citations